Temporal Asymmetry in the Molecular World - Aquilano, Roberto Oscar (2017)
The asymmetry of time is important to approach the cellular world, especially to understand stem cells and cancer. As the amount of energy involved in microscopic processes is so small, it is more difficult to argue that entropy increases, and therefore the direction of time becomes confusing and undefined at the molecular level. This is an extension of a previous work, where some details are specified and alternatives are proposed.